2016
DOI: 10.1021/acs.joc.6b01555
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Hydrosilylation/Cyclization of 1,6-Enynes

Abstract: An iminopyridine cobalt dichloride complex was synthesized and demonstrated as an effective precatalyst for hydrosilylation/cyclization of 1,6-enynes with silanes. Various functional groups such as amine, free aniline, ester, ether, cyano, halide, trifluoromethyl, and heterocycle were tolerated to afford a variety of silicon-containing compounds. The reaction could be scaled up to afford products on the gram scale which could undergo further derivatizations. A primary mechanism was proposed based on analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…(2) and 2.271(1), 2.3523(8), 2.421(1), respectively). [28] The distance between the two copper centres in 3 is 3.540 and that between the two cobalt centres in 4 is 3.418 and these distances lie within the range reported for related chlorobridged dimeric complexes. [27,28]…”
Section: 139supporting
confidence: 69%
See 1 more Smart Citation
“…(2) and 2.271(1), 2.3523(8), 2.421(1), respectively). [28] The distance between the two copper centres in 3 is 3.540 and that between the two cobalt centres in 4 is 3.418 and these distances lie within the range reported for related chlorobridged dimeric complexes. [27,28]…”
Section: 139supporting
confidence: 69%
“…The Cu‐N and Cu‐Cl distances (2.076(2), 2.000(2) and 2.2008(8), 2.2724(8), 2.678(1) Å, respectively) in 3 are comparable with those found in similar pyridylimine derived chloro‐bridged dimeric Cu(II) complexes . Similarly, the Co‐N and Co‐Cl distances (2.117(3), 2.124(3) and 2.261(1), 2.370(1), 2.399(1)Å, respectively) in 4 are comparable with those for diisopropylphenyl(pyridyl)imine derived chloro‐bridged dimeric Co(II) complex (2.109(2), 2.139(2) and 2.271(1), 2.3523(8), 2.421(1)Å, respectively) . The distance between the two copper centres in 3 is 3.540 Å and that between the two cobalt centres in 4 is 3.418 Å and these distances lie within the range reported for related chloro‐bridged dimeric complexes ,…”
Section: Resultsmentioning
confidence: 65%
“…[245] In 2016, Lu and co-workers developed a cobalt-catalyzed hydrosilylation/cyclization of 1,6-enynes with a simple iminopyridine Chin. [245] In 2016, Lu and co-workers developed a cobalt-catalyzed hydrosilylation/cyclization of 1,6-enynes with a simple iminopyridine Chin.…”
Section: Co-catalyzed Hydrosilylation Of the Other Multiple C-c Bondsmentioning
confidence: 99%
“…The Ni complex exhibited high catalytic activity towards the hydrosilylation of secondary hydrosilanes with yields of up to 93% and high selectivity for mono-hydrosilylation. Lu et al reported an iminopyridine complex of cobalt dichloride as catalyst for the combined hydrosilylation and cyclization of 1,6-enynes ( Figure 13) [35]. This reaction could be scaled-up to the gram scale.…”
Section: Nickel Catalystsmentioning
confidence: 99%
“…A pincer complex of the composition ( tBu P C NN iPr )CoCl2 was found to deliver highest yields with respect to the regio-and Z-selectivity after activation by NaH·BEt3. Lu et al reported an iminopyridine complex of cobalt dichloride as catalyst for the combined hydrosilylation and cyclization of 1,6-enynes ( Figure 13) [35]. This reaction could be scaled-up to the gram scale.…”
Section: Nickel Catalystsmentioning
confidence: 99%